STUDENT DIFFICULTIES ON STRUCTURE AND WRITTEN EXPRESSION SECTION OF TOEFL IN HIGHER EDUCATION AT METRO CITY - Yeasy Agustina Sari; Suhono; Suryawahyuni Latief; Umar Al Faruq A. Hasyim (Curricula : Journal of Teaching and Learning, 2021)
Structure and Written Expression TOEFL is a major difficulty for students because of the lack of TOEFL understanding preparation, no specific TOEFL preparation book has been used, and the inaccurate use of strategies in understanding TOEFL. The purpose of this study was to analyze students' English language skills in the TOEFL Structure and Written Expression section material, to analyze the difficulties of the Structure and Written Expression material for students, and to describe the reasons for the difficulties faced by students in the Structure and Written Expression material. This research uses a descriptive method. The random sampling technique was carried out with a total sample size of 30 students in the English Language Study Program at Higher Education, namely the Islamic Institute of Islamic Studies Ma'arif Metro Lampung and IAIN Metro Lampung. Data collection techniques using tests, interviews, and observations. The test given in this study is the TOEFL Paper Based Test (PBT) published by the Educational Testing Service (ETS). The findings in this study have shown that  students experience difficulties on the Structure and Written Expression of TOEFL because their ability in the test is at level C, "Enough". Second, among the eight indicators of the Structure and Written Expression material tested in the TOEFL, Inversion is the most difficult answer for students to answer because they have never studied this material and in-depth analysis is needed to answer the question. This shows that from the two TOEFL Structure tests the percentage of material difficulty is the highest among the other seven indicators.